Synthesis of CoxMn1−xO4 (0.9≤x≤2.7) nanopowders with controlled phase and composition via a gel-combustion method. Issue 15 (15th November 2016) - Han, HyukSu; Lee, Jae Seok; Lim, Jiun; Park, Kyoung Ryeol; Kim, Kang Min; Ryu, Jeong Ho; Yeo, Sunghwan; Forrester, Jennifer; Mhin, Sungwook
Abstract: Cox Mn3−x O4 (CMO) nanopowders with a wide compositional range (0.9 ≤ x ≤ 2.7) are synthesized using a gel combustion method. The effect of Co content and calcination temperature on the crystal structure of the CMO nanopowders is studied using X-ray diffraction. A highly crystalline cubic spinel structure can be obtained at a relatively low temperature ( 700 °C) for CMO with a Co content of 1.8. Further increases in Co content to 2.7 leads to a higher formation temperature ( 800 °C) required in order to form a crystalline cubic structure. X-ray photoelectron spectroscopy revealed that the Co and Mn cations have mixed valence states. Energy dispersive X-ray elemental mapping indicates that Co and Mn cations are homogeneously distributed in the CMO nanopowders. Thermogravimetric analysis, Fourier transform infrared, scanning electron microscopy, and X-ray fluorescence are utilized to investigate the formation of the CMO nanopowders, as well as the compositional and structural properties.